Die representasie van die visie in die verhalende prosa van Elsabe Steenberg - Van der Westhuizen, Elizabeth Susanna (My University, 1997)
Elsabe Steenberg's oeuvre, consisting among others of forty two stories in book format, has four target groups -- preschool children, young children, teenagers and adults. Her narrative work is so richly textured and contains such a depth of insight into the complexities of life that it should not only attract attention because of its topicality, but that it should also be exposed -- especially in a society searching for direction -- to as large a number of readers and researchers as possible. It is clear that all of her works represent a view of reality which, from an intertextual point of view, could be seen as being grounded in the ontological point of departure. The main focus of the present study is to investigate the representational procedes through which the ontological view is represented in four selected texts from the oeuvre. This is done in order to establish internal textual variants and constants. The four selected texts, in which tree symbolism manifests itself in various intertextual permutations, are: Die boom wat wou loop (for preschool children), Soek-soek op soek (for young children), Boom homer boomste (for teenagers) and Plek van die bruin geeste (for adults). The rest of the oeuvre, as well as Elsabe Steenberg's poetics, are referred to cursorily in order to establish a corroborating intertextual comparative base. The procedes representing the whole internal textual universe, from concrete object, • through the different but also complementary narrative elements, further to the overt representation and manifestation of the abstract theme and view of the narrative world, are all investigated. The four texts are first discussed independently by means of a structuralist-semiotic approach, after which the variants and constants are determined intertextually. The numerous aspects of the representational system of the view of reality in all four the intensively studied texts, as well as those in the rest of the oeuvre which are only touched on briefly, an point toward one fundamental factor as semiotic sign, namely: God is. Identity as an intertextual constant plays a very prominent role in the whole oeuvre. Consequently, the numerous ways in which the fundamental view of reality are represented, are thus also associated with God's identity or Being, for example, God is the Origin, God is the Giver of insight into the diversity, interrelatedness and meaning of reality, and God is the real regenerating Force.
Proefskrif (PhD (Afrikaans en Nederlands))--PU vir CHO, 1997.
Keywords: Elsabé Steenberg; Representation; View of reality; Poetics; Semiotics; Tree symbolism; Literature for preschool children; Literature for young children; Children's literature; Youth literature; Intertextuality